2016
DOI: 10.3109/0886022x.2016.1144031
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipid profile with serum PON1 concentration in patients with chronic kidney disease

Abstract: Patients with chronic kidney disease (CKD) are at high risk of atherosclerotic events; dyslipoproteinemia and the decrease of the HDL-linked enzyme paraoxonase 1 (PON1), might have a major role. This study intends to compare the association between lipid profile and serum PON1 levels in renal failure (RF) and hemodialysis (HD) patients. Serum lipids, HDL-subclasses and PON1 concentration were evaluated in 90 patients with CKD, divided into groups: RF (n ¼ 46) and HD (n ¼ 44), and in 30 normal individuals (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
2
16
0
7
Order By: Relevance
“…It was shown that although serum PON1 concentration is significantly reduced only in HD patients, PON3 is significantly elevated (about 2.7 times) in CKD and about four times in HD patients compared to the controls. Regarding PON1 concentration, similar low values were reported for pre‐dialysis and dialysis patients . There are limited data, however, about the concentration of PON3 in CKD.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…It was shown that although serum PON1 concentration is significantly reduced only in HD patients, PON3 is significantly elevated (about 2.7 times) in CKD and about four times in HD patients compared to the controls. Regarding PON1 concentration, similar low values were reported for pre‐dialysis and dialysis patients . There are limited data, however, about the concentration of PON3 in CKD.…”
Section: Discussionsupporting
confidence: 62%
“…Regarding paraoxonases, recent reports, however, show that statins and especially atorvastatin therapy increase serum HDL‐associated PON activity in patients with dyslipidemia . In the present study, the inclusion of statin‐treated patients was based on the results of our previous report , which showed that statin therapy marginally affects the concentration of PON1 in either CKD or HD patients. Finally, because of the observational nature of this study, the inferences about the relationship between endocan and PON1 levels have hypothetical cause‐effect character and additional markers of endothelial dysfunction could give a better insight about the role of paraoxonases on the prevention of atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…PON1 activity is substantially lower in patients with CAD, ACS, CKD, and RA, whereas lipoprotein-associated phospholipase A 2 (LpPLA 2 ) activity is increased in CKD and psoriasis (89,137,160,165,(171)(172)(173)(174)(175). Dysregulating the activity of PON1 and LpPLA 2 in this fashion not only compromises the antioxidative activity of HDL, but also promotes the formation of atherosclerotic plaques.…”
Section: Composition and Role Of Hdl-associated Proteinsmentioning
confidence: 99%